The Formation and “Decay” of Xlla - Speer, R. J; Ridgway, Helen (Thrombosis and Haemostasis, 1967)
Various materials and conditions have been investigated for their effect on Hageman factor activation. Fatty acid soaps, purified phospholipids, ellagic acid, platelets, and freezing and thawing were among those studied.Under certain circumstances XIIa activity disappeared spontaneously; the factors affecting the kinetics of this “decay” have been evaluated. Successful regeneration of this “decayed” XII a has been achieved. On the basis of these observations, it is postulated that during its “decay”, XIIa reverts to XII by spontaneous molecular refolding.